2022
DOI: 10.1371/journal.pone.0266142
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness of medications for opioid-related disorders: A systematic review and network meta-analysis of randomized controlled trials

Abstract: Introduction Several pharmacotherapeutic interventions are available for maintenance treatment for opioid-related disorders. However, previous meta-analyses have been limited to pairwise comparisons of these interventions, and their efficacy relative to all others remains unclear. Our objective was to unify findings from different healthcare practices and generate evidence to strengthen clinical treatment protocols for the most widely prescribed medications for opioid-use disorders. Methods We searched Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 116 publications
1
13
0
Order By: Relevance
“…MOUD combined with psychosocial interventions is the most effective treatment option for patients suffering from OUD ( ASAM, 2020 ; Connock et al., 2007 ; Dugosh et al., 2016 ). MOUD has been shown to be associated with positive outcomes for reducing drug use, criminal activity ( Gisev et al., 2019 ; Gossop et al., 2000 ; Oliver et al., 2010 ; Røislien et al., 2014 ), risk behaviors and HIV-transmission ( Marsch 1998 ), overdoses, and overall mortality ( Gisev et al., 2015 ; Sordo et al., 2017 ) as well as improving rates of retention in treatment ( Lim et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…MOUD combined with psychosocial interventions is the most effective treatment option for patients suffering from OUD ( ASAM, 2020 ; Connock et al., 2007 ; Dugosh et al., 2016 ). MOUD has been shown to be associated with positive outcomes for reducing drug use, criminal activity ( Gisev et al., 2019 ; Gossop et al., 2000 ; Oliver et al., 2010 ; Røislien et al., 2014 ), risk behaviors and HIV-transmission ( Marsch 1998 ), overdoses, and overall mortality ( Gisev et al., 2015 ; Sordo et al., 2017 ) as well as improving rates of retention in treatment ( Lim et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous systematic review of 14 studies revealed non-statistically significant results for successful completion of treatment (OR = 0.78; 95% CI, 0.34–1.75) and use of opioids under treatment (OR = 0.85; 95% CI, 0.45–1.62) ( 35 ). A network meta-analysis conducted by Lim and colleagues which aimed to evaluate the effectiveness of different medication types for opioid-related disorders showed that the likelihood of treatment retention was statistically significantly higher for naltrexone than for controls [relative risk (RR) = 1.54; 95% CI, 1.26–1.90], and showed the average percent of treatment retention of 41.0% for naltrexone among all included studies ( 36 ). Furthermore, the RRs for the effectiveness of naltrexone compared with buprenorphine, methadone, and slow-release oral morphine were 0.72 (95% CI, 0.55–0.91), 0.59 (95% CI, 0.45–0.77), and 0.62 (95% CI, 0.38–0.99), respectively ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A network meta-analysis conducted by Lim and colleagues which aimed to evaluate the effectiveness of different medication types for opioid-related disorders showed that the likelihood of treatment retention was statistically significantly higher for naltrexone than for controls [relative risk (RR) = 1.54; 95% CI, 1.26–1.90], and showed the average percent of treatment retention of 41.0% for naltrexone among all included studies ( 36 ). Furthermore, the RRs for the effectiveness of naltrexone compared with buprenorphine, methadone, and slow-release oral morphine were 0.72 (95% CI, 0.55–0.91), 0.59 (95% CI, 0.45–0.77), and 0.62 (95% CI, 0.38–0.99), respectively ( 36 ). Our study showed that naltrexone increased retention to treatment by 63.8% compared to the control group, which was not significant (95% CI, 0.78–3.44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there is limited evidence regarding the effectiveness of various doses of BUP‐NX and methadone in the treatment of OUD for people who mainly use prescription‐type opioids (from prescription or unregulated sources), and not heroin. Most efficacy studies were conducted when heroin was the main opioid used, with only a few studies having been conducted in people with OUD since the use of extremely potent opioids such as fentanyl has become common 8,22 . Also, these studies have been conducted in clinical settings with stricter OAT dosing schedules so that results cannot be confidently used to guide practice in real‐world clinical settings in which flexible OAT doses are implemented 8,22 .…”
Section: Introductionmentioning
confidence: 99%